2021
DOI: 10.1186/s13049-021-00936-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of delayed bleeding in patients on antiplatelet therapy after mild traumatic brain injury: a systematic review and meta-analysis

Abstract: Background The scientific evidence regarding the risk of delayed intracranial bleeding (DB) after mild traumatic brain injury (MTBI) in patients administered an antiplatelet agent (APA) is scant and incomplete. In addition, no consensus exists on the utility of a routine repeated head computed tomography (CT) scan in these patients. Objective The aim of this study was to evaluate the risk of DB after MTBI in patients administered an APA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In mild TBI patients treated with APAs, two meta-analyses have demonstrated a small increased risk of immediate ICH, especially if concomitant with another risk factor for ICH such as GCS < 15 or age > 65 years [ 363 ] and a very low risk of delayed ICH [ 364 ], respectively. However, the subgroup of patients on dual antiplatelet therapy had an increased delayed bleeding risk, compared with single APA patients [ 364 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mild TBI patients treated with APAs, two meta-analyses have demonstrated a small increased risk of immediate ICH, especially if concomitant with another risk factor for ICH such as GCS < 15 or age > 65 years [ 363 ] and a very low risk of delayed ICH [ 364 ], respectively. However, the subgroup of patients on dual antiplatelet therapy had an increased delayed bleeding risk, compared with single APA patients [ 364 ].…”
Section: Resultsmentioning
confidence: 99%
“…In mild TBI patients treated with APAs, two meta-analyses have demonstrated a small increased risk of immediate ICH, especially if concomitant with another risk factor for ICH such as GCS < 15 or age > 65 years [ 363 ] and a very low risk of delayed ICH [ 364 ], respectively. However, the subgroup of patients on dual antiplatelet therapy had an increased delayed bleeding risk, compared with single APA patients [ 364 ]. Another meta-analysis that included 20 observational studies comparing 2447 TBI patients on pre-injury APAs with 4814 controls revealed no statistically significant difference in early mortality, need for neurosurgery or LOS between the two groups, with similar results for subgroup analyses of aspirin and clopidogrel users [ 365 ].…”
Section: Resultsmentioning
confidence: 99%
“…55 Another meta-analysis showed a risk of dICH in mTBI patients using APT of 0.18%. 56 Therefore, the authors of these two studies concluded that, for most patients, discharge after an initial negative head CT is defendable. There is a lack of data on the need for observation or repeat CT head in elderly mTBI patients specifically using DOACs in case of a negative CT. We found no difference in the rate of dICH between elderly mTBI patients using DOACs compared to patients using APT or VKAs.…”
Section: Discussionmentioning
confidence: 99%
“…In our population, we had no delayed bleeding or differences in those on AT, even in those onclopidogrel, even if predisposed to it [ 27 ]. Of the five patients on AC with active bleeding, 3/5 were on warfarin.…”
Section: Discussionmentioning
confidence: 99%